2022
DOI: 10.7150/jca.75754
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of MUC6 Genetic Variants on the Clinicopathologic Characteristics of Patients with Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the leading malignancy associated with cancer-related deaths worldwide. Many studies have indicated that mucin (MUC) expression plays an important role in cancer metastasis and recurrence. MUC6 expression is observed in gastric and oncocytic phenotypes and may play an important role during cancer progression. We found the level of MUC6 is lower in HCC patients but did not affect the survival of HCC patients. Therefore, in this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…In our previous study, we found that genetic variations in MUC6 may correlate to hepatocellular carcinoma and indicate the progression in hepatocellular carcinoma patients. 23 Research has revealed that the methylation of the MUC6 promoter may cause a considerable decrease in MUC6 expression in gastric cancer and drive its progression. 21 Furthermore, we found low MUC6 expression reduced the risk of OSCC.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we found that genetic variations in MUC6 may correlate to hepatocellular carcinoma and indicate the progression in hepatocellular carcinoma patients. 23 Research has revealed that the methylation of the MUC6 promoter may cause a considerable decrease in MUC6 expression in gastric cancer and drive its progression. 21 Furthermore, we found low MUC6 expression reduced the risk of OSCC.…”
Section: Introductionmentioning
confidence: 99%